Determination of fructose and some mineral elements concentration in the seminal plasma of rams - Anam Hamza; sarab sulayman; Mohammed Hamza (College of Education for Pure Sciences, 2012)
Abstract The study included determination of ram's semens concentration in 22 samples collected by using artificial vagina with averag of one ejaculate for aweak. The sperm concentration was (2x 109 /ml) and the percentage of life sperms obtained by using the eosin dye (85%) in addition to the use of Trypan blue to show the intact acrosome. The result showed the concentration of fructose in seminal plasma was (21± 6 mmol/ L) The study also included the measurement of the elements concentrations of (zinc, magnesium, calcium, sodium, potassium, and nickel) in ram seminal plasma and the result showed that the order of these concentrations of Na, k, Ca, Zn, Mg, Ni have been decreased respectivly. The presence of these elements in ram semen could have different rols to play in the survival and function of spermatozoa.